2012
DOI: 10.1504/ijaape.2012.043965
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the value relevance of total comprehensive income under IFRS: an empirical evidence from European stock exchanges

Abstract: This paper compares the value relevance of the net income and the total comprehensive income reported under IFRSs. The total comprehensive income represents a key measure of the overall company performance, and it is extremely topical after the revision of the IAS 1. The paper aims at verifying whether the total comprehensive income is more value relevant than the net income. To this purpose, accounting and market data regarding companies listed on the UK, French, German, Spanish and Italian stock exchanges ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 47 publications
2
18
0
1
Order By: Relevance
“…These results are consistent with previous literature (e.g. Devalle et al (2010Devalle et al ( , 2012. For the 2006-2009 period France, Spain, Germany and Italy report that comprehensive income is more value relevant than the net income, but opposite findings arise from the model estimation that consider only data collected before the financial crisis: the data collected referring to the financial statements of the years before financial crisis show that comprehensive income is not so value relevant as in the post-crisis scenario.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These results are consistent with previous literature (e.g. Devalle et al (2010Devalle et al ( , 2012. For the 2006-2009 period France, Spain, Germany and Italy report that comprehensive income is more value relevant than the net income, but opposite findings arise from the model estimation that consider only data collected before the financial crisis: the data collected referring to the financial statements of the years before financial crisis show that comprehensive income is not so value relevant as in the post-crisis scenario.…”
Section: Resultssupporting
confidence: 91%
“…In order to assess whether comprehensive income is more meaningful for investors than net income, a value relevance approach has been used in this study in compliance with Devalle et al (2012). Commonly, value relevance studies on comprehensive income use various versions of the Price Regression Model (Kanagaretnam et al, 2009;Barth et al, 2008;Dastgir and Velashani, 2008;Pinto, 2005;Cahan et al, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…Huang et al (2014) also found that the lack of accounting standards requirement for comprehensive income reporting in China affect value relevance of comprehensive income. Moreover, Devalle and Magarini (2012) and Zülch and Pronobis (2010) also found no evidence on value relevance of comprehensive income. Devalle and Magarini (2012) Zülch and Pronobis (2010) found no evidence on value relevance of comprehensive income.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Prior to the introduction of the statement of comprehensive income, serious concerns have been raised about income items that are undisclosed in the income statement which in turn reduce the transparency of financial statements and consequently decrease the value relevance of financial information to investors and other users (Devalle & Magarini 2012;Kanagaretnam, Mathieu & Shehata 2009;Smith 2017). The income statement presents only the consequences of the ordinary and regular operations for the current period while non-operating or non-recurring items are excluded from net income.…”
Section: Introductionmentioning
confidence: 99%
“…Os resultados líquido e integral têm sido objeto de estudos que se debruçam sobre o seu poder explicativo (Chambers, Linsmeier, Shakespeare & Sougiannis, 2007;Cheng, Cheung & Gopalakrishnan, 1993;Devalle & Magarini, 2012;Dhaliwal, Stibramanyam & Trezevant, 1999). O interesse pelas componentes do ori, designadamente as resultantes de revalorizações de ativos (Aboody, Barth & Kasznik, 1999;Barth & Clinch, 1998;O'Hanlon & Pope, 1999) e das reservas resultantes da conversão cambial (Dhaliwal et al, 1999;O'Hanlon & Pope, 1999) estiveram, desde cedo, presentes, contudo numa abordagem em que a sua relevância é analisada por item, e não de forma conjunta.…”
Section: Enquadramento Teórico E Hipótesesunclassified